Why Organised Cancer Screening Works: Lessons from Slovenia and the Next Phase of Evidence-Based Implementation - Mateja Krajc; Urška Ivanuš (Slovenian Journal of Public Health, 2026)
Abstract Slovenia's experience shows that cancer screening becomes effective only when a test is embedded in an organised, population-based programme that reaches the target population equitably, assures quality across the whole pathway and uses individual- and programme-level data for improvement. Since the national roll-out of Programme ZORA for cervical cancer screening in 2003, followed by DORA for breast cancer screening in 2008 and Programme Svit for colorectal cancer screening in 2009, Slovenia has built a coherent screening infrastructure with visible population effects. Cervical and colorectal cancer incidence and mortality are decreasing, breast cancers detected through DORA are increasingly diagnosed at a localised stage, and Slovenia ranks among the strongest European performers in screening coverage and policy. This editorial argues that these achievements should be understood not as three isolated programme successes, but as the result of governance, registries, quality assurance, legal foundations, public trust and international alignment. The same principles must now guide the modernisation of existing programmes and the cautious, evidence-based introduction of lung, prostate and gastric cancer screening.